Which factors determine the gender gap in the entrepreneurial action? Evidence from Mexico. (1st August 2019) - Saiz-Álvarez, José Manuel; Rodríguez-Aceves, Lucía
The empirical evidence about how the gender gap influences on the entrepreneurial intention (EI) and its effects on the entrepreneurial action (EA) are still limited. The objective of this paper is to analyse the main factors to explain the entrepreneurial gender gap in Mexico related to EI and EA and moderated by income, education, and marital status. Our findings show that, first, although women have a high EI in Mexico, they are reluctant to create firms due to an upper perceived behavioural control (PBC), so their EA is deficient. As a result, the Mexican labour market continues being very traditional with low rates of female participation. Second, the EI tends to decrease with income. Third, single men with completed graduate and/or postgraduate studies and high levels of income are more prone to entrepreneurship in Mexico.